Análise energética e exergética de um sistema de alto desempenho de um grupo: motor de combustão interna a gás natural - alternador síncrono - Cavalcante, Antonio Wilton Araújo (2015)
This paper presents the development of a High Performance System (HPS). The project has three setting developed that analyzes the performance in quantity and quality energy for a generator engine Group (GEG) 100 KVA inserted in settings. For each study, the behavior of energy flows are decouple, making it possible to analyze the best structure of the HPS. The unit constituints of the project were a subsystem cooling by absorbing water – ammonia chiller, a heat recover and a biodiesel production plant. It with these subsystems will work separately characterizing them as cogeneration systems. After that it will be integrated all in one system and then classified as trigeneration system. This work also aims to analyze the behavior of electric charges by energy analyzer and temperature by thermal imager.